An Exploration of a Boston Green New Deal Policy Platform - Masters, Julia. (Tufts University. Tisch Library., 2021)
Thesis (M.A.)--Tufts University, 2020.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Loh.; Committee: Kristin Skrabut.; Keyword: Environmental justice.; The Green New Deal is a policy framework, introduced nationally, for addressing the climate and economic crises.  Through decarbonization, public ownership, and public investment, the Green New Deal aims to prioritize public goals over corporate profits, target investments to marginalized communities, and create green jobs.  Lack of federal urgency on combating climate change has complicated the national visioning process — but has made room for local and state Green New Deal discourse, which have a range of different jurisdictional powers. The Boston Green New Deal is being developed through values of solidarity and equity. Beyond city-level conversations, state Green New Deal brainstorming sessions have also convened. There are innovative ways to approach the Green New Deal framing to leverage local work, and this research intends to illuminate visioning of those processes, which has implications and learnings for the vast range of Green New Deal brainstorming happening around the country.